2020
DOI: 10.1007/978-3-030-59065-9_20
|View full text |Cite
|
Sign up to set email alerts
|

Cyberbullying Detection in Social Networks Using Deep Learning Based Models

Abstract: Cyberbullying is a disturbing online misbehaviour with troubling consequences. It appears in different forms, and in most of the social networks, it is in textual format. Automatic detection of such incidents requires intelligent systems. Most of the existing studies have approached this problem with conventional machine learning models and the majority of the developed models in these studies are adaptable to a single social network at a time. In recent studies, deep learning based models have found their way… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 16 publications
0
34
0
Order By: Relevance
“…The experiments of the proposed model are conducted using Intel core i7@4GHz with 16 GB of RAM running on windows 10 platform and implemented using Python v2.7. The following eight different machine learning algorithms have been utilized to discover an optimal combination of base-classifiers in the initial stage and the meta-classifier in the second one: SVM, 38 NB, 28 DNN, 36 CNN, 34 RF, 39 AdaBoost, 37 LR, 39 and Bagging. 26 Table 2 displays the parameter settings of these classification algorithms and Table 3 showcases the empirically adjusted base-classifiers' hyper-parameter settings for different datasets.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experiments of the proposed model are conducted using Intel core i7@4GHz with 16 GB of RAM running on windows 10 platform and implemented using Python v2.7. The following eight different machine learning algorithms have been utilized to discover an optimal combination of base-classifiers in the initial stage and the meta-classifier in the second one: SVM, 38 NB, 28 DNN, 36 CNN, 34 RF, 39 AdaBoost, 37 LR, 39 and Bagging. 26 Table 2 displays the parameter settings of these classification algorithms and Table 3 showcases the empirically adjusted base-classifiers' hyper-parameter settings for different datasets.…”
Section: Resultsmentioning
confidence: 99%
“…Proposed model beat the best-known results for the datasets procured from Wikipedia, Twitter, and Formspring. Dadvar et al 36 proposed a Deep Neural Network (DNN)-based model for cyberbullying detection in social media platforms and extended their work to examine the transferability and adaptability of the model by using new dataset from YouTube social media. Rafiq et al 37 designed a multi-stage cyberbullying detection system that lessens the classification time dramatically and highly responsive in raising alerts without sacrificing accuracy.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Various heterogeneous graph neural networks are often used to understand the social characters of the users, such as the users' emotions, personality types, and interests [37]. Dadvar et al [38,39] performed a reproducibility study with deep learning based models that are conducted in [29], their reproduced experiment showed that deep learning based models with word embedding outperform the machine learning models, they also thought the effect of oversampling method should be assessed.…”
Section: Cyberbullying Detectionmentioning
confidence: 99%
“…Another direction focuses on the testing generalization of the current hatespeech classifiers (Agrawal and Awekar, 2018;Dadvar and Eckert, 2018;Gröndahl et al, 2018), where those methods are tested in other datasets and domains such as Twitter data (Waseem and Hovy, 2016), Wikipedia data (Wulczyn et al, 2017), Formspring data (Reynolds et al, 2011), and YouTube comment data (Dadvar et al, 2014).…”
Section: Related Workmentioning
confidence: 99%